Synthetic Spatial Foraging With Active Inference in a Geocaching Task - Neacsu, Victorita; Convertino, Laura; Friston, Karl J. (Frontiers in Neuroscience, 2022)
Humans are highly proficient in learning about the environments in which they operate. They form flexible spatial representations of their surroundings that can be leveraged with ease during spatial foraging and navigation. To capture these abilities, we present a deep Active Inference model of goal-directed behaviour, and the accompanying belief updating. Active Inference rests upon optimising Bayesian beliefs to maximise model evidence or marginal likelihood. Bayesian beliefs are probability distributions over the causes of observable outcomes. These causes include an agent’s actions, which enables one to treat planning as inference. We use simulations of a geocaching task to elucidate the belief updating - that underwrites spatial foraging - and the associated behavioural and neurophysiological responses. In a geocaching task, the aim is to find hidden objects in the environment using spatial coordinates. Here, synthetic agents learn about the environment via inference and learning (e.g., learning about the likelihoods of outcomes given latent states) to reach a target location, and then forage locally to discover the hidden object that offers clues for the next location.